Treaty Series 3189 - United Nations Office of Legal Affairs (United Nations, 2025)
In accordance with Article 102 of the Charter and the relevant General Assembly Resolutions, every treaty and international agreement registered or filed and recorded with the Secretariat since 1945 is published in the United Nations Treaty Series. At present, the collection includes about 30,000 treaties reproduced in their authentic languages, together with translations into English and French, as necessary.